Determination of Sensitivity of Influenza Virus Strain A(H7N9) to Antiviral Drugs In Vitro and In Vivo - M. A. Skarnovich; M. O. Skarnovich; L. N. Shishkina; N. I. Bormotov; A. B. Ryzhikov; A. P. Agafonov (Антибиотики и Химиотерапия, 2020)
The phenotypic sensitivity of the influenza virus strain A/Anhui/1/2013 (H7N9) to antiviral drugs with different mechanisms of action in the MDCK cell culture and in outbred ICR mice experiments was observed. The A/Anhui/1/2013 (H7N9) strain of influenza virus showed the highest sensitivity to Tamiflu in in vitro experiments, whereas the sensitivity of this influenza virus strain to Rimantadine and Ingavirin was less pronounced. The A/Anhui/1/2013 (H7N9) strain exhibited absolute sensitivity only to Tamiflu in in vivo studies of such factors as virus titers in the lungs, the protection factor, and the average life expectancy of the animals. The sensitivity of this strain of influenza virus to Ingavirin was not detected in dose and administration regimen used in vivo. Rimantadine sensitivity of this strain in vivo was significantly weaker than to Tamiflu, and manifested only in reducing viral titers in the lungs 3 days after the mice were infected.